Investigating the Effects of Using Google Classroom on the Student’s Engagement in Writing Instruction During Covid-19 Outbreak - Annisa, Nova Nurul; Friatin, Lilies Yulia (Journal of English Education Program (JEEP), 2024)
English is a foreign language that has been taught from elementary school to tertiary level. The aim of teaching English in junior high school is to help recognizing word structures well. The present study were focused on 1) examining the student’s engagement in the online classroom during a pandemic situation and more specifically on descriptive text lessons; 2) investigating how teachers use Google Classroom in teaching and how the students learning activity use Google Classroom as an online platform. This study aimed to investigate the effect of using Google Classroom on student engagement in learning during this pandemic. The participant in this study is one English teacher and thirty students in one of junior high schools in Ciamis. This research approach is qualitative with the type of case study. The present study employs observation and in-depth interviews to collect the data. This study used a qualitative descriptive analysis methodology consisting of data reduction, data display, conclusion, and verification. Completed data is obtained by the data collection process then the data must be analysed and interpreted. Based on the research that has been done, the effect of using Google Classroom in this junior high school is not too influential on the learning process. The reason is that many students cannot access the internet because of the network conditions where they live. So, the English teachers use other learning apps as a tool to help the teaching and learning process of their students so that they can continue to follow the lesson.